2019
DOI: 10.1007/s10035-019-0940-4
|View full text |Cite
|
Sign up to set email alerts
|

Jamming transition in non-spherical particle systems: pentagons versus disks

Abstract: We investigate the jamming transition in a quasi-2D granular material composed of regular pentagons or disks subjected to quasistatic uniaxial compression. We report six major findings based on experiments with monodisperse photoelastic particles with static friction coefficient µ ≈ 1. (1) For both pentagons and disks, the onset of rigidity occurs when the average coordination number of non-rattlers, Z nr , reaches 3, and the dependence of Z nr on the packing fraction φ changes again when Z nr reaches 4. (2) T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Over two decades ago, it was first proposed [1][2][3] that soft and granular materials can have a jammed, solid phase, which forms at sufficiently high packing fraction or pressure, and sufficiently low shear and temperature. Now, much is known about materials in the vicinity of the zero-temperature jamming threshold, ''Point J''; not only for simple models like soft or hard repulsive, frictionless spheres, [4][5][6][7] but for particles which are non-spherical, [8][9][10][11][12] have rough and/or frictional surfaces, 13,14 are confined within various wall geometries [15][16][17] and even active matter [18][19][20] (including work on active matter in the presence of fixed obstacles 21 ). For frictionless soft spheres, a mixed firstsecond order phase transition, with upper critical dimension of d = 2 occurs 6,[22][23][24] at a maximally random close packing fraction (MRP).…”
Section: Introductionmentioning
confidence: 99%
“…Over two decades ago, it was first proposed [1][2][3] that soft and granular materials can have a jammed, solid phase, which forms at sufficiently high packing fraction or pressure, and sufficiently low shear and temperature. Now, much is known about materials in the vicinity of the zero-temperature jamming threshold, ''Point J''; not only for simple models like soft or hard repulsive, frictionless spheres, [4][5][6][7] but for particles which are non-spherical, [8][9][10][11][12] have rough and/or frictional surfaces, 13,14 are confined within various wall geometries [15][16][17] and even active matter [18][19][20] (including work on active matter in the presence of fixed obstacles 21 ). For frictionless soft spheres, a mixed firstsecond order phase transition, with upper critical dimension of d = 2 occurs 6,[22][23][24] at a maximally random close packing fraction (MRP).…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in Fig. 1, the intruder leaves a channel in its wake as it pushes through the system; local packing fractions outside of the channel and for a stable cluster of grains in front of the intruder are significantly closer to the expected frictional jamming fraction ∼ 0.78 [15]. The difference between the global packing fractions for disks and pentagons can thus be largely attributed to the fact that the size of the cluster of particles in front of the intruder is significantly smaller for pentagons than for disks.…”
Section: Intruder Dynamicsmentioning
confidence: 76%
“…Recent studies of granular media composed of grains of a variety of shapes have shown that non-spherical/noncircular grains, which feature additional rotational resistance at the grain-grain interaction scale [9] , better represent measurable bulk parameters like shear strength [10][11][12][13], relative viscosity [14] in sheared suspensions, and jamming packing fraction [15] observed in real systems.…”
Section: Introductionmentioning
confidence: 99%
“…Interlocking geometries can be utilized to create kinematic constraints to only allow for motion in particular directions. [ 31–35,53–57 ] Fibers can have prismatic cross sections, rather than circular ones to avoid kinematic rearrangement in particular directions and to transform the contact lines between constituents into contact surfaces. [ 14 ] Particles can be designed with particular geometries to create larger number of contact points, or larger contact surface areas between the particles.…”
Section: Resultsmentioning
confidence: 99%